Homicide in pre-famine and famine Ireland - Mc Mahon, Richard (Liverpool Univ. Press, 2013)
The title provides a quantitative and contextual analysis of homicide in pre-famine and famine Ireland, placing the Irish experience within a comparative framework and drawing wider inferences about the history of interpersonal violence in Europe and beyond